The use of lorcaserin in the management of obesity: a critical appraisal - Bo Bai; Yu Wang (Dove Medical Press, 2010)
Bo Bai, Yu WangDepartment of Pharmacology and Pharmacy, Li Ka Shing Faculty of Medicine, University of Hong Kong, Hong Kong, People’s Republic of ChinaAbstract: Obesity is a chronic disease with a high prevalence in both developed and developing countries. Effective management of this worldwide epidemic will have a significant impact on the health care system globally. Lifestyle interventions, such as restricting calorie consumption and increasing physical activity, remain a major component of weight-reduction programs. The development of pharmacotherapy for the management of obesity is still at the infancy stage. Side effects have been the key issue for anti-obesity drugs previously withdrawn from the market. The focus of this review, lorcaserin, is a selective serotonin receptor agonist that is currently undergoing Phase III evaluations. The efficacy of this drug in reducing body weight and improving metabolic parameters of obese patients has been demonstrated in two recent clinical trials. The available evidence indicates that this drug does not show unwanted effects on heart valves or pulmonary artery pressure, and the treatment improves the risk factors for type 2 diabetes and cardiovascular diseases. Despite these promising results, additional experimental and clinical studies are critical for the approval of lorcaserin as a new anti-obesity monodrug therapy by the US Food and Drug Administration.Keywords: obesity, anti-obesity drug, 5-hydroxytryptamine receptor agonist, clinical trial